Peninjauan dan Pembuatan Peta Proses Bisnis Sebagai Salah Satu Program Pengembangan Organisasi - Wustari L. Mangundjaya (CV. ULIL ALBAB CORP, 2024)
To be exist and develop, every organization have to conduct many interventions including revisit the business process, as it was assumed is no longer updated anymore. The objective of this paper is to discuss about the implementation of new business process and RACI at the service company. Results showed that revisiting and revising the business process is needed as business process will be the guidance of the organization. In this regard, involvement of the job holder is very critical and become the key success in achieving the effective business process and RACI.